DEVELOPING ENGLISH READING MATERIAL BY USING GENRE BASED APPROACH FOR GRADE X OF BEAUTY PROGRAM AT SMK PARIWISATA IMELDA MEDAN - Teresa Erganita Br Ginting; Indra Hartoyo (Universitas Negeri Medan, 2021)
The aim of this study was to (1) find out the learning needs of X grade of Beauty Program students at SMK Pariwisata Imelda Medan in improving their reading skills, (2) develop relevant reading materials by using Genre Based Approach for X grade students of Beauty Program at SMK Pariwisata Imelda Medan. This research was conducted by using Research and Development which is adapted from Borg, Gall and Gall (2003). The data was taken from the observation, questionnaires, and interview. The materials were validated by an English lecture and an English teacher by using validation sheets which is adapted from BSNP. The data were collected by using descriptive analysis. The result of this study shows that: (1) the existing materials do not support the students major because the topics of the materials are still general, (2) relevant reading materials are needed by students in vocational school especially in Beauty Program. These materials were developed by using Genre Based Approach, (3) the developed reading materials by using Genre Based had been validated with the score 3.69 from expert 1 and 3.83 from expert 2 which is in the range of 3.25 < ≤ 4.00. These materials have been developed in accordance to the students’ need by using Genre Based Approach.Keywords: English reading materials, Genre Based Approach, Vocational High School